2018
DOI: 10.3748/wjg.v24.i4.537
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary bile duct adenocarcinoma and gastrointestinal stromal tumor in a case of neurofibromatosis type 1

Abstract: We report our experience with a synchronous case of gastrointestinal stromal tumor (GIST) and intraductal papillary neoplasm of the bile duct (IPNB) in an elderly woman with neurofibromatosis type 1 (NF-1). A 72-year-old woman presented with a 2-mo history of right upper abdominal pain unrelated to diet and indigestion. Fourteen years earlier, she had been diagnosed with NF-1, which manifested as café au lait spots and multiple nodules on the skin. Computed tomography (CT) revealed a multilocular low-density m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…(2) Other diseases: IPNB and gastrointestinal stromal tumor and neurofibromatosis type 1 were found in a case of neurofibromatosis type 1 [ 61 ]. There have also been rare cases of IPNB in liver cirrhosis patients [ 62 ].…”
Section: Clinical Features Epidemiology and Imaging And Endoscopimentioning
confidence: 99%
“…(2) Other diseases: IPNB and gastrointestinal stromal tumor and neurofibromatosis type 1 were found in a case of neurofibromatosis type 1 [ 61 ]. There have also been rare cases of IPNB in liver cirrhosis patients [ 62 ].…”
Section: Clinical Features Epidemiology and Imaging And Endoscopimentioning
confidence: 99%
“…It has also been reported that individuals with NF1 may have an increased susceptibility to other neoplasms [ 13 ]. Recent studies have suggested that NF1 may also play a role in breast tumors [ 23 ], colorectal cancer [ 24 ], pancreatic ductal adenocarcinoma [ 25 ], gastrointestinal stromal tumor (GIST), and neoplasm of the bile duct [ 26 ]. Despite these findings, it remains unclear how NF1 contributes to the pathogenesis of these malignancies, and its role in GBC remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%